Neurogenic Inflammation Involves in Systemic Spread of Oral Infection - Utomo, Haryono (Journal of Dentistry Indonesia, 2014)
Focal infection theory proposed in early 1900’s stated that dental infection caused systemic disorders. Nevertheless, the theory was abandoned since large number of teeth were extracted with no satisfying result. Recent reports revealed that oral infections were able to spread systemically. However, there is no rationalization available to explain how assisted drainage therapy (ADT), a periodontal therapy that could relief migraine and asthma within minutes. Oral neurogenic and immunogenic inflammation interaction involving pro-inflammatory markers such as calcitonin gene-related peptide (CGRP), TNF-α; and antiinflammatory vasoactive intestinal peptide (VIP) was still under investigation. Objective: To verify the spread of oral inflammation to distant organ after performing ADT by analysing CGRP, VIP and TNF-α expressions. Methods: Two different concentration of Porphyromonas gingivalis lipopolysaccharide (PgLPS1435/1450) was injected intragingivally into two groups of 12 Wistar rats. After four days, 12 rats were given ADT and all samples were subsequently sacrificed 40 mins after ADT. Immunohistochemistry analysis using CGRP, VIP and TNF-α on the nasal and bronchus tissue was performed. ANOVA was used for statistical analyisis of the difference between CGRP, VIP and TNF-α expression between experimental groups. Results: PgLPS injections slightly increased CGRP, VIP and TNF-α expressions in the control group. Rats undergone ADT had lower CGRP and TNF-α but higher VIP expressions. Conclusion: Neurogenic inflammation involved in systemic sp